The Influence of Traditional Religious Authority on Digital Preachers: Case Studies of Ustadz Hanan Attaki and Ustadz Adi Hidayat - Rozy, Yahya Fathur (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This research aims to investigate whether traditional religious authorities in the case of two largest Islamic organizations in Indonesia (Nahdlatul Ulama and Muhammadiyah) still have greater authority than the new media friendly religious figures. This research employs the bai’at (edification) of Ustadz Hanan Attaki (UHA) to Nahdlatul Ulama and the admission of Ustadz Adi Hidayat (UAH) to the Muhammadiyah General Board as a case study. This research attemps to answer two questions: How do new religious authorities still need to rely on traditional religious authorities? Why are the traditional religious authorities in NU & Muhammadiyah still able to survive during the development of new media and the emergence of new religious authorities? Using the theoretical framework of Max Weber, this study explains the process of forming authority. This research finds that first, new religious authorities lack key elements of "authority." The long-established structures within traditional groups provide a level of legitimacy that is difficult for new religious authorities to replicate without integrating into these networks. Second, traditional authorities have spent decades, even centuries, building a loyal following and strong organizational infrastructure. These networks are supported by political capital, granting traditional authorities protection, and influence that new figures cannot easily access.